Influence of foreign language anxiety and motivation toward English language achievement among UMK students - Yoga Rafinika (2020)
Today, language is a vital source of communication. It is how people share their thoughts, views, feelings, and ideas among themselves. Language distinguishes people from other kinds of animals and makes them human. There are thousands of languages in this world. In today’s global world, the importance of English cannot be denied and ignored since it is the broadest common language spoken universally. Today’s business society drives all organizations to adapt to use English as the global language of business. Amount of multinational companies that are mandating English as the common corporate language is increasing. Companies are attempting to facilitate performance and communication across geographically diverse functions and business ventures. The fact that the factors of personality traits may well shape success in acquiring a Foreign Language (FL). Critical areas of the present research are the investigation of the influences of Anxiety and Motivation in learning FL that influence the English Learning Achievement. Based on the identified measurement variables, from previous studies, a questionnaire was developed and operated for the present research. After the respondents agreed to fulfil the questionnaire, the google form link that leads to the research’s questionnaire was given to the participants. Fortunately, from all the contacted members in UMK student group, only 140 respondents were collected, and only 134 completed questionnaires were suitable for further analysis. After that, descriptive analysis was conducted based on the data collected from the samples and reliability test was carried out to ensure satisfactory internal consistency, validity, and reliability. The final process for extracting result based on the collected data is to proceed, which is statistical analysis. Present research conducted correlation analysis and regression analysis to extract the result of testing the hypotheses. Findings of the present research have shown that amongst two variables, only FL Anxiety that gives negative significance to English Achievement; however, FL Motivation was not giving any significant relation toward English Achievement. Moreover, FL Motivation all three subscales, Intrinsic Motivation, Extrinsic Motivation, and Amotivation, gave significant influence to FL Anxiety. However, only Intrinsic Motivation gave negative influence on FL Anxiety. It means that with an intervention program to improve the Intrinsic Motivation level of a learner, their FL Anxiety can be decreased.